Evaluation of dispersion and damage sensing of carbon fiber/polypropylene (PP)-polyamide (PA) composites using 2 dimensional electrical resistance mapping. (November 2016) - Kwon, Dong-Jun; Shin, Pyeong-Su; Kim, Jong-Hyun; DeVries, K. Lawrence; Park, Joung-Man
Abstract: This paper evaluated the potential use of carbon fiber/polypropylene-polyamide (CF/PP-PA) composites in thermoplastic automobile applications. Two dimensional electrical resistance (2D ER) mapping was use to sense and predict damages. The extent of random dispersion of carbon fibers (CF) in PP-PA matrix was evaluated using 2D ER mapping contour charts. ER data collected at 9 different positions was used to evaluate dispersion and micro-damages. The uniformity of dispersion of CF in fractured surfaces was observed for comparison. Pyrolyzed specimens were used to measure CF amount in each part and compared with 2D ER mapping. The differences in ER for tensile and compressive stresses were compared to explore their usage for real time monitoring and sensing of damages. The observation of the fractured surfaces exhibited an acceptable consistency with 2D ER results. Ultimately 2D ER mapping should be useful for evaluating and predicting damages in CF/PP-PA composites under various loading conditions.